Oral health assessment during Covid-19 pandemic: community self-report questionnaire - Felisha Febriane BALAFIF; Agus SUSANTO; Indah Suasani WAHYUNI (Journal of Syiah Kuala Dentistry Society, 2021)
ABSTRACT The Covid-19 pandemic situation has affected community activities, work, income whichdecreased, psychological disorders such as stress, and limited accessibility to dental practice service,which is now for emergency cases only. This condition can affect oral health in the community. Thisstudy aimed to assess the oral health condition in the community during the Covid-19 pandemic. Thisstudy was implementing a cross-sectional research design. Data were obtained from onlinequestionnaires with the respondent's consent. The sample selection with inclusion criteria comprised 1960yearsoldwholivedinBandungWestJava.Theself-reportquestionnairefororalhealthassessmentwasfollowed,thepreviousresearch,byLevinetal.,2013.Ithasbeentrans-adaptedtoBahasaIndonesiaandvalidated.Respondentsofthestudywere380participants.Poororalhygienemaintenancewasthewrongfrequencyofbrushingteeth(12.1%),onlyvisitingthedentistwhenhavingatoothache(72.9%),andsmoking(7.9%).Oralhealthproblemsincludegingivalbleedingonbrushing(15.3%),toothmobility(13.2%),tooth cavities (62.9%), toothache (27.1%), and bad breath (22.6%). Most of the oral healthproblems were tooth cavities followed by toothache. The contributing factors include poor oral hygienemaintenance, improper brushing, smoking habits, and infrequent dental care. Furthermore, theaccessibility and availability of services in dental practice in the pandemic situation are limited.Therefore, it is reasonable to say that oral self-examination probably could minimize the distancingrelatedprobleminthisCovid-19pandemicsituationandbehelpfulintheearlydetectionoforalhealthproblems.KEYWORDS: assessment, Covid-19 pandemic, oral health